THE EFFECT OF WORD WALL METHOD ON STUDENTS’ WRITING ABILITY - Hetty Zaharani (Universitas Potensi Utama, 2021)
Writing is one of the important skills in teaching English. But in writing, there are some obstacles to construct sentences and express ideas. Usually, the common problems are lack of knowledge about grammar, vocabulary, and content. Many people are restricted by their skill of writing and caused them can not express their idea in writing. Many great ideas cannot breakthrough because they were never been written or show up. To face this common problem, there must be some ways and solutions to improve the students’ writing ability, in this case, the researcher used the word wall method in helping students to improve their writing ability. This research aims to figure out whether the word wall method can improve students’ writing ability. The subject of this research was the tenth students of Nahdatul Ulama’s School in the academic year 2020/2021 that consisted of 40 students in X class, 22 females and 18 males. Based on the result of the research, the writing ability of the students was increased by applying the word wall method in the first cycle. In the pre-test, before treatment, the mean figure was 38. After applying the word wall method in cycle 1, the figure increased to 57 and in the cycle, the mean figure achieved 82 points. It could be stated that the students got a significant improvement in their writing ability. This condition occurred because some weaknesses that appeared in cycle one had been revised and implemented well in cycle two. It could be concluded that the effect of the word wall method could be able to change positively the writing ability of students with significantly value.